36 Medical Physicist and Radiologists, a winning team: Definition of a new biomarker for the assessment of small aortic aneurysm rapid growth risk. (December 2018) - Moreno, R.; Meyrignac, O.; Zadro, C.; Sewonu, A.; Bartoli, J.M; Rousseau, H.; Piquet, P.; Bal, L.
Abstract : Introduction: Abdominal Aortic Aneurysm (AAA) is a common pathology which treatment decision is mostly made upon measurement of maximal diameter, despite known limitations. Thanks to the collaboration between Medical Physicist and Radiologist, this study aimed to identify new biomarkers based on computational fluid dynamics (CFD) analysis to predict AAAs rapid growth risk. Methods: In our multi-centric and prospective study, we included 78 patients with an AAA from September 2012 to June 2014. Patients underwent two CT examinations separated by a one-year interval to assess aneurysms growth. Fifty patients underwent CFD analysis thanks to the Medical Physicist expertise. Based on a 10 ml threshold of total volume growth, we classified patients into slow and rapid growth groups. Aneurysms initial morphological and functional parameters were analyzed including: maximal diameter and surface, thrombus and lumen volumes, maximal wall pressure and wall shear stress (WSS). Results: There was a significant difference between the two groups regarding aneurysm lumen volume (P = 0.0051) and mean WSS variation (P = 0.0240) unlike maximal diameter (P = 0.71). We found significant correlation of aneurysm volume growth with lumen volume and reduction of the mean WSS variation value (respectively R = 0.47, P = 0.0015 and R = −0.42, P = 0.0062) and total aneurysm volume growth. Combining these parameters, we computed an AAAs growth-predicting model, which featured better area under ROC than the only measurement of maximal diameter (0.78 vs 0.52, P = 0.0031). Depending on the threshold, our model yields either excellent sensitivity (95.00% [IC95% 75.1, 99.9]) or specificity (90.00% [IC95% 73.5, 97.9]). Conclusions: Tight collaboration between Medical Physicist and Radiologists allowed to find a promising biomarker based on CFD which provides better information than maximal diameter to assess rapid AAAs volume growth risk.